PENGARUH TERAPI NON FARMAKOLOGI YOGURT TERHADAP PENURUNAN TEKANAN DARAH IBU HAMIL HIPERTENSI DI PUSKESMAS GAYAMANKECAMATAN GAYAMAN KAB. MOJOKERTO - Diana, Sulis (JURNAL KEPERAWATAN BINA SEHAT, 2016)
Hypertension in pregnancy can cause maternal morbidity and even death of the fetus. This research aimed to know the influence of non – farmacology theraphy on decreasing of mother’s blood pressure with hipertension in RSUD Mojokerto and Puskesmas Gayaman Mojokerto.This research used Quasi Experiment design on three groups.Respondets recive treatment that was yogurt consumptions for 2 weeks. .The group of yoghurt, 45 respondents as sampling. Conducted in a year in Puskesmas Gayaman. Analyzed with Wilcoxon rang test and Kolmogorov-Smirrov at the level p ≤ 0,05There was a difference in blood pressure before and after given: dengan p value (0,013) < a (0,05, The result of wilcoxon test showed that Z count value was -2,489-2,489 with P value (0.013) < a (0,05) so that ho was rejected the blood presware before and after the given of yoghurt therapy.yoghurt is one of menu that can be on alternative solusion for decreasing of blood pressure on pregnant mothers with hypertention that is safe for the feture. The consumption of yoghurt as may as 2-3 timer a day ( minimum 142ml/day and maximum 1600ml/day).Key words : yoghurt, hypertension, pregnancy.